Analysis of the Relationship between Health Center Management and Service Quality at Pon Village Health Center, Serdang Bedagai Regency in 2024 - Manurung, Tetty Grace Manurung; Karnirius Harefa; Novita Br. Ginting Munthe (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Health Center Management is a series of planning, organizing, implementing and controlling processes to achieve targets/objectives effectively and efficiently. Objective: This study aims to analyze the relationship between Health Center management and service quality at Pon Village Health Center, Serdang Bedagai Regency. Research Method: This type of research is quantitative research in the form of an analytical survey with a cross-sectional design. Results: The results of the study showed that bivariately all variables, namely planning (P1), implementation (P2) and supervision (P3) had a significant value <0.05. Multivariately based on candidate selection, it was obtained that the three variables were eligible to be included in the multivariate model because the significant value was P <0.25. The final result of the logistic regression obtained that only 2 variables were included in the final regression model, namely implementation (p 0.003) and supervision (p 0.003). And the most related variable is supervision with Exp (B) 55.594. Conclusion: there is a relationship between health center management consisting of planning, implementation and supervision of the quality of service at the Health Center. It is expected that the Head of the Health Center must really carry out a series of management processes, starting from planning, because from the results of the study there were still respondents who answered that the planning was not good, as well as the implementation, even from the results of the study it was found that supervision was not running well at the Pon Village Health Center. For this reason, the Head of the Health Center must increase supervision routinely. So that the management process is really implemented, to achieve maximum service.